PENGARUH PENGGUNAAN MEDIA STORYJUMPER TERHADAP KETERAMPILAN MENULIS TEKS NARASI SISWA KELAS XII SMA ADVENT AIR BERSIH MEDAN TAHUN 2025/2026 - Paska Elmaria Sitorus; Monalisa Frince S; Elza Leyli Lisnora Saragih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine students' narrative writing skills before and after using StoryJumper learning media and the effect of its use on the narrative writing skills of 12th-grade students at SMA Advent Air Bersih Medan. This study used a quantitative approach with an experimental method and a one-group pretest-posttest design. The study sample consisted of 40 students. Data collection techniques were conducted through pretests and posttests in narrative writing. Data were analyzed using mean scores, normality tests, homogeneity tests, and t-tests. The results showed that students' narrative writing skills before using StoryJumper media averaged 59.95, with a lowest score of 45 and a highest score of 75. After using StoryJumper media, they increased to an average score of 79.28, a lowest score of 65, and a highest score of 95. The results of the hypothesis test showed that the calculated t of 11.793 was greater than the t table of 1.685 at a significance level of 0.05, thus Ha was accepted and Ho was rejected. Thus, the use of StoryJumper media had a significant effect on the narrative text writing skills of class XII students of SMA Advent Air Bersih Medan.